Adhesion of Human Probiotic Lactobacillus rhamnosus to Cervical and Vaginal Cells and Interaction with Vaginosis-Associated Pathogens. (27th January 2009) - Coudeyras, Sophie; Jugie, Gwendoline; Vermerie, Marion; Forestier, Christiane
Abstract : Objectives . The ability of a probiotic Lactobacillus rhamnosus strain (Lcr35) to adhere to cervical and vaginal cells and to affect the viability of two main vaginosis-associated pathogens, Prevotella bivia, Gardnerella vaginalis, as well as Candida albicans was investigated. Methods . Adhesion ability was determined in vitro with immortalized epithelial cells from the endocervix, ectocervix, and vagina. Coculture experiments were performed to count viable pathogens cells in the presence of Lcr35. Results . Lcr35 was able to specifically and rapidly adhere to the three cell lines. In coculture assays, a decrease in pathogen cell division rate was observed as from 4 hours of incubation and bactericidal activity after a longer period of incubation, mostly with P. bivia . Conclusion . The ability of Lcr35 to adhere to cervicovaginal cells and its antagonist activities against vaginosis-associated pathogens suggest that this probiotic strain is a promising candidate for use in therapy.